Evidence-based practice for occupational therapists - Taylor, Clare M., ....- (Oxford : Blackwell Science, 2000)
Contents:---------IntroductionFinding the evidenceUsing clinical trials as evidenceSystematic reviewsQualitative research as evidenceMaking evidence-based practice workUseful resources.Evidence-based practice is one of the driving forces in currenthealthcare practice. Occupational therapists recognize the need forresearch and for an evidence-based approach to intervention, yet they mayneed guidance on how to achieve this. This book makes evidence-basedpractice accessible and relevant to occupational therapists, usingexamples from therapy practice.
Keywords: Evidence based practice -- Ergotherapie